As A Roman City Aelia Capitolina/Jerusalem - Celebi, Azize Gelir; Pilehvarian, Nuran Kara (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2023)
The relationship between Jerusalem and the Roman Empire, which has a deep-rooted history, dates to It began in 63 BC. when the Roman leader Pompeius captured the city. Thus, the Roman domination of Jerusalem, which would last for about seven centuries, began. In 37 BC, during the reign of King Herod, the city, and the temple (built by King Solomon) were repaired, and an amphitheater and hippodrome were added to the city's zoning plan. The Roman Emperor Hadrianus (117-138 AD) restructured the city, which was destroyed because of the rebellion in 135 and had Aelia Capitolina designed following the Hippodamos plan. One of the most important features of Roman city planning is that it was created parallel to two main artery/road axes in the north-south (Cardo Maximus) and east-west (Decumanus Maximus) directions This plan in the literature is called grid/ Hippodamian plan/chessboard, and it has been known since Hippodamos of Miletus in the 5th century BC. After coming under Roman domination, Jerusalem was shaped according to this plan like other Roman cities. The article focuses on the historical process of Jerusalem (old city- inner the wall) in the Roman Empire period and the shaping of the city plan according to the Roman period road texture, traces of which can still be read today. Readings were made on the Madaba Mosaic Map and the Crusader Maps, the oldest visual source where the Roman period road texture can be seen. The oldest known period of today's urban texture of Jerusalem has been tried to be revealed with sources and period readings.
Keywords: Jerusalem; Rome City Plan; Aelia Capitolina; Cardo Maximus; Decumanus Maximus; Roman Empire; Byzantine Empire; Art